Time Traveller - "Bull, Angela" (Dorling Kindersley: London, 1999)
Sophie & Jake take a journey they'll never forget thanks to some computer software and a time traveller called Whirligig. Col. illus., glossary, information boxes. 7 yrs+
Keywords: World history Juvenile